Modern Pedagogical Technologies For Developing Students' Speech In Primary Grades - Radjapova Yulduzhan Alisherovna (Euro Asian Journal Publishing, 2024)
This article analyzes the importance, methods and effectiveness of using modern pedagogical technologies to develop students' speech in primary grades. Developing students' speech helps to develop not only language skills, but also students' skills such as creativity, communication, and fluent expression of thought. The article shows the role and importance of modern technologies, including interactive educational platforms, mobile applications, digital tools and gaming technologies, in developing speech. An analysis is also presented, including how these technologies help students learn new knowledge more easily and effectively.
Keywords: Primary grades; student speech; pedagogical technologies